Changes in physicochemical and biological properties of porcine bone derived hydroxyapatite induced by the incorporation of fluoride. Issue 1 (1st January 2017) - Qiao, Wei; Liu, Quan; Li, Zhipeng; Zhang, Hanqing; Chen, Zhuofan
Abstract: As the main inorganic component of xenogenic bone graft material, bone-derived biological apatite (BAp) has been widely used in implant dentistry, oral and maxillofacial surgery and orthopedics. However, BAp produced via calcination of animal bones still suffers from some drawbacks, such as insufficient mechanical strength and inadequate degradation rate, which impede its application. Fluoride is known to play important roles in both physiological and pathological processes of human hard tissues for its double effects on bones and teeth. In order to understand the effects of fluoride on the properties of BAp, as well as the mechanism behind them, porcine bone derived hydroxyapatite (PHAp) was prepared via thermal treatment, which was then fluoride incorporated at a series concentrations of sodium fluoride, and noted as 0.25-FPHAp, 0.50-FPHAp, and 0.75-FPHAp respectively. The physicochemical characteristics of the materials, including crystal morphology, crystallinity, functional groups, elemental composition, compressive strength, porosity and solubility, were then determined. The biological properties, such as protein adsorption and cell attachment, were also evaluated. It was found that the spheroid-like crystals of PHAp were changed into rod-like after fluoride substitution, resulting in a fluoride concentration-dependent increase in compressive strength, as well as a decreased porosity and solubility of the apatite. However, even though the addition of fluoride was demonstrated to enhance protein adsorption and cell attachment of the materials, the most favorable results were intriguingly achieved in FPHAp with the least fluoride content. Collectively, low level of fluoride incorporation is proposed promising for the modification of clinically used BAp based bone substitute materials, because of its being able to maintain a good balance between physicochemical and biological properties of the apatite. Abstract :